A novel Ti cored wire developed for wire-feed arc deposition of TiB/Ti composite coating. (30th August 2021) - Bao, Yang; Huang, Lujun; Jiang, Shan; Zhang, Rui; An, Qi; Zhang, Caiwei; Geng, Lin; Ma, Xinxin
Graphical abstract: Highlights: Synthesize TiB/Ti composite coating with high hardness by depositing a newly-developed Ti-TiB2 cored wire. Reaction mechanism and droplet transfer behavior of cored wire were revealed. Variation of TiB whiskers' distribution with welding current was related to molten pool flow. Hardness enhancement was ascribed to load-sharing strengthening of TiB whiskers. Abstract: A novel Ti cored wire containing TiB2, Al60V40 and Ti6Al4V mixed powders was developed for wire-feed arc deposition of TiB/Ti composite coating, to enhance the hardness and wear resistance of Ti alloy. Results showed that after experiencing several chemical reactions, the wire was melted in the arc zone and turned into nonuniform droplets composed of Ti-Al-V-B melt and undecomposed TiB2 particles. With the increase of welding current, the detachment time of droplet shortened while the transfer frequency accelerated, accompanied by the improvement in coating surface quality. The spatial distribution of TiB whiskers in coating was governed by welding current. A uniform distribution could be achieved as welding current was sufficient at the expense of elevated dilution ratio, while increasing wire feeding speed could compensate the dilution loss of TiB whisker to some extent. The decomposition process of TiB2 particles and the microstructure evolution mechanism of coating was discussed in detail. The optimum coating possessed uniform microstructure, relatively low dilution ratio, and high hardness (639.1 HV0.5 ) as compared with Ti6Al4V substrate (326 HV0.5 ). Indentation morphology analysis verified the excellent performance was ascribed to the load-sharing strengthening of TiB whiskers. This study provides a high-efficiency fabrication method for the ever-developing titanium matrix composites (TMCs) coating.